Implementasi Teori Belajar Kognitif Pada Kurikulum 2013 - Azzahra Aulia Yuliadi; Hindun Hindun (Lembaga Pengembangan Kinerja Dosen, 2024)
This research discusses efforts to introduce cognitive learning theory into the 2013 curriculum in the educational environment. Her research focus is on understanding how key principles of cognitive learning theory, including concepts such as information processing, knowledge construction, and the development of higher-order thinking skills, can be integrated into new curriculum structures. Research methods include analysis of official 2013 curriculum documents, interviews with teachers, and observation of classroom learning practices. The results show that although real efforts have been made to adopt the principles of cognitive learning theory, their implementation still faces certain challenges. Limited resources, teacher understanding of cognitive concepts, and adaptation of learning materials are several important factors that influence successful implementation. Therefore, this research provides recommendations for improving teacher training, adapting learning materials, and increasing resource support so that the 2013 curriculum more effectively achieves students' cognitive learning goals.